2022
DOI: 10.55215/pedagonal.v6i2.5612
|View full text |Cite
|
Sign up to set email alerts
|

Improving Teacher Organizational Citizenship Behavior (OCB) through Servant Leadership, Justice and Self-efficacy: Indonesian Teacher Perspective

Abstract: The different roles of teacher behavior or organizational citizenship behavior (OCB) can be a lifesaver for schools. This study aims to find strategies to improve such behaviors. This study uses a quantitative approach with path analysis using SMART PLS. The population and sample of this study were 243 junior high school teachers in Bogor Regency, West Java, Indonesia. The main findings of this study are that improving teacher OCB will be faster and more effective if it is done with improved Servant leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…The direct causal link of knowledge management, teaching performance and faculty spirituality towards organizational citizenship behavior among sectarian private school teachers in Davao Region corroborates the research outcomes revealed by Lavy (2019) that teachers experience a greater sense of ownership and autonomy when they are empowered through application and information sharing, which improves their organizational citizenship behavior. Nonetheless, Hidayat and Patras (2022) posited that there isn't always a strong correlation between teachers' knowledgesharing practices and organizational learning cultures. Teachers' sharing of knowledge may be more strongly influenced by other organizational and individual characteristics, such as organizational commitment and work satisfaction.…”
Section: Best Fit Model Of Organizational Citizenship Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The direct causal link of knowledge management, teaching performance and faculty spirituality towards organizational citizenship behavior among sectarian private school teachers in Davao Region corroborates the research outcomes revealed by Lavy (2019) that teachers experience a greater sense of ownership and autonomy when they are empowered through application and information sharing, which improves their organizational citizenship behavior. Nonetheless, Hidayat and Patras (2022) posited that there isn't always a strong correlation between teachers' knowledgesharing practices and organizational learning cultures. Teachers' sharing of knowledge may be more strongly influenced by other organizational and individual characteristics, such as organizational commitment and work satisfaction.…”
Section: Best Fit Model Of Organizational Citizenship Behaviormentioning
confidence: 99%
“…Teachers experience a greater sense of ownership and autonomy when they are empowered through application and information sharing, which improves their organizational citizenship behavior (Lavy, 2019). However, teachers' sharing of knowledge may be more strongly influenced by other organizational and individual characteristics, such as organizational commitment and work satisfaction (Hidayat & Patras, 2022). Several studies have found a positive relationship between teachers' organizational citizenship behavior and teaching performance (Arib, 2021;Ali et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…OCB plays a fundamental role in improving school effectiveness [ 7 ]. In the era of Society 5.0, teachers face various challenges [ 8 ], and advances in communication technology and changes in society require teachers to demonstrate high OCB, because teachers have an important role in schools [ 9 ]. OCB is essential in the teaching profession [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…OCB from teachers is demonstrated through helpful behavior towards colleagues, supervisors, and students who need help (including assistance with exam preparation practice) and contributing to the school (for example, providing recommendations for changes and improvements and suggestions that are useful for the school) [ 11 ]. Principal leadership can help improve teacher OCB at different levels [ 9 ]. One of the factors that predict OCB is leadership.…”
Section: Introductionmentioning
confidence: 99%